2015
DOI: 10.5194/isprsarchives-xl-7-w3-1511-2015
|View full text |Cite
|
Sign up to set email alerts
|

Can single empirical algorithms accurately predict inland shallow water quality status from high resolution, multi-sensor, multi-temporal satellite data?

Abstract: ABSTRACT:Assessing and monitoring water quality status through timely, cost effective and accurate manner is of fundamental importance for numerous environmental management and policy making purposes. Therefore, there is a current need for validated methodologies which can effectively exploit, in an unsupervised way, the enormous amount of earth observation imaging datasets from various high-resolution satellite multispectral sensors. To this end, many research efforts are based on building concrete relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The variation of EC in a water body is related to changes in the concentration of total dissolved solids in the water. The increase in the salinity of the water causes changes in the amount of radiation reflected in the visible and infrared spectrum bands (Khattab & Merkel, 2013;Theologou et al, 2015). Further, pH was related to bands b3, b4, b5, and b6 with R 2 of 0.8153. pH is the negative logarithm of the concentration of H + ions and has also been linked with the band b6 (Theologou et al, 2015).…”
Section: Statistical Models Of Water Quality and Depthmentioning
confidence: 98%
“…The variation of EC in a water body is related to changes in the concentration of total dissolved solids in the water. The increase in the salinity of the water causes changes in the amount of radiation reflected in the visible and infrared spectrum bands (Khattab & Merkel, 2013;Theologou et al, 2015). Further, pH was related to bands b3, b4, b5, and b6 with R 2 of 0.8153. pH is the negative logarithm of the concentration of H + ions and has also been linked with the band b6 (Theologou et al, 2015).…”
Section: Statistical Models Of Water Quality and Depthmentioning
confidence: 98%
“…Shen et al [63] and Ruddick et al [64] also successfully applied the spectral reflectance at Red-NIR region to detect and monitor harmful algal bloom at inland and coastal waters. Theologou et al [65] also found a high correlation of Chl-a with red and NIR regions of Landsat 7 and 8 satellite for predicting water quality in inland shallow lakes.…”
Section: Development Of the Prediction Modelmentioning
confidence: 91%
“…Similarly other studies like Dogliotti et al (2015) tested wavelength bands (645 and 859 nm) to extract turbidity parameter. A ratio between the blue (Band 2) and red bands (Band 4) was proposed by Theologou et al (2015) to retrieve dissolved oxygen with Landsat 8 images of a lake located in Greece and achieved an accuracy of 0.80 R 2 . In 2015 (Bonansea et al 2015), Landsat TM and Landsat ETMþ data were compared with field data for a lake in Argentina.…”
Section: Related Workmentioning
confidence: 99%
“…Dissolved Oxygen (DO) was calculated with the estimation algorithm proposed by Theologou et al (2015), and Khalil et al (2016). They used a combination of TOA reflectance of Bands 2 and 4, which can be seen in Equation (3).…”
Section: Dissolved Oxygenmentioning
confidence: 99%